AB0041 DO FUNCTIONAL INTERACTIONS BETWEEN MACROPHAGES AND SYNOVIAL FIBROBLASTS DRIVE SYNOVIAL PATHOLOGY OR RESOLUTION OF INFLAMMATION?. (June 2019) - Elmesmari, Aziza; Benson, Robert; Macdonald, Lucy; Finlay, Samuel; Filer, Andrew; Alivernini, Stefano; Vaughan, Diane; Tolusso, Barbara; Gremese, Elisa; Mcinnes, Iain; Clark, Andy; Kurowska-Stolarska, Mariola
Abstract : Background: We recently uncovered heterogeneity in human synovial tissue macrophages during inflammation and resolution of inflammation (remission) in rheumatoid arthritis (RA). The transcriptomic profiles of distinct macrophage subpopulations suggest distinct functions, ranging from inflammatory to regulatory. Prior studies propose reciprocal interactions between macrophages and synovial fibroblasts (FLS) exist in the joint; however, the exact contribution of these interactions to synovial pathology or resolution of inflammation remains unknown. Objectives: The aim of this study was to examine the functional interactions between different macrophage phenotypes and synovial fibroblasts. Methods: To model different macrophage phenotypes, monocyte-derived macrophages (MODM) were pre-stimulated (16h) with LPS (100ng/ml) to model inflammatory macrophages or with dexamethasone (Dex, 1μM) to model regulatory macrophages. After extensive washing, MODM were co-cultured with RA FLS for different periods of time. Prior to co-culture, FLS and MODM were labelled with CellTraceTM-Violet and CellTraceTM-Red, respectively. After 24 & 48 hours of co-culture, FLS and MODM were sorted based on positivity for CellTraceTM Violet (FLS) or Far Red (MODM) using FACS ARIA III, and expression of IL-6 and MMP1 in FLS analysed by ultrasensitive qPCR. In addition, the levels of IL-6 and MMP3 proteins were evaluated in co-culture supernatants by ELISA. To investigate the nature of the contact (40min meandering velocity) of individual MODMs on FLS monolayers was evaluated using Delta Vision fluorescence microscopy. Results: FLS co-cultured with MODM showed an increased mRNA expression of IL-6 at both 24 and 48h, and MMP1 at 48h, compared to FLS cultured alone. This expression pattern was decreased when MODM were pre-treated with Dex and significantly up regulated when MODM were pre-treated with LPS. Consistently with mRNA expression, IL-6 protein was significantly increased when FLS were co-cultured with MODM (1192±137pg/ml) as compared to FLS cultured alone (445±78pg/ml). This production was significantly augmented when MODM were pre-treated with LPS (1985±25 pg/ml) and decreased when MODM were pre-treated with Dex (729±62pg/ml). Similarly, MMP3 protein level was increased when FLS were co-cultured with MODM (256±10pg/ml) as compared to FLS cultured alone (123±1 pg/ml). This production was significantly augmented when MODM were pre-treated with LPS (1960±34pg/ml) and decreased when MODM pre-treated with Dex (164±2pg/ml). These distinct effects of MODM phenotypes on FLS function were associated with different dynamics of their interactions. Our preliminary data reveal that MODM are quiescent on FLS monolayers unless MODM are pre-treated with Dex, which induced a patrolling behaviour. Conclusion: Macrophages can actively increase or limit activation of FLS, depending on their inflammatory or regulatory phenotypes, respectively. These observations indicate the potential for different subsets of synovial tissue macrophages to drive or resolve synovial inflammation by influencing the stromal compartment. References: [1] Elmesmari A, Alivernini S, et al., Synovial tissue of RA patients in remission contains a unique population of regulatory macrophages. Annals of the Rheumatic Diseases, 2017;76 (Suppl2) 138-139. Disclosure of Interests: Aziza Elmesmari: None declared, Robert Benson: None declared, Lucy MacDonald : None declared, Samuel Finlay : None declared, Andrew Filer: None declared, Stefano Alivernini Speakers bureau: BMS, Diane Vaughan: None declared, Barbara Tolusso: None declared, Elisa Gremese Consultant for: AbbVie, BMS, Celgene, Janssen, Lilly, MSD, Novartis, Sanofi, UCB, Roche, and Pfizer, Speakers bureau: BMS, Speakers bureau: Roche, Speakers bureau: AbbVie, BMS, Celgene, Janssen, Lilly, MSD, Novartis, Sanofi, UCB, Roche, and Pfizer, Iain McInnes Grant/research support from: AstraZeneca, Celgene, Compugen, Novartis, Roche, UCB Pharma, Consultant for: AbbVie, Celgene, Galvani, Lilly, Novartis, Pfizer, UCB Pharma, Andy Clark : None declared, Mariola Kurowska-Stolarska: None declared